ORGANIZATION OF COMPUTER DEVICES for IMPLEMENTATION OF THE MAC FUNCTION ON THE BASIS OF PLIS - Opanasenko , V. N.; Lisovy , A. N. (Problems of Informatization and Control, 2021)
The structural implementation of the function of multiplication-accumulation in the elementary basis of FPGAs of FPGA type, performed by the behavioral description of the algorithm in the VHDL language, is proposed. Checking the functioning of the module by the modeling method in the ModelSim Xilinx Edition - МХЕ 11 system using a test stand has been implemented.